Backstepping sliding-mode techniques in current control of polymer electrolyte membrane fuel cell. (July 2022) - Yin, Peng; Guo, Jinquan; He, Hongwen
Abstract: The polymer electrolyte membrane fuel cell (PEMFC) power conditioning is particularly crucial for a fuel cell vehicle to meet various load demands effectively. This paper focuses on the PEMFC current control addressing varied tracking references or disturbance injections. With control-oriented models of the PEMFC-fed DC–DC systems, two control methods integrated with sliding-mode control (SMC) are proposed to regulate the fuel cell current: a backstepping method dealing with high nonlinearity and coupled characteristics of the PEMFC power supply, and an adaptive approach counteracting parametric uncertainties or load disturbances. Simulations and experiments indicate that the proposed backstepping SMC could alleviate chattering of the conventional SMC effectively and maintain good robustness; in addition, the adaptive backstepping SMC could further reduce the fuel cells ′ settling time by 25 % during transient response experiment with the boost converter and make system parameters vary more smoothly with the buck converter. Highlights: A control-oriented model of the PEMFC-fed DC–DC power supply is established. Both boost converter and buck converter are involved in the PEMFC output regulation. The proposed backstepping SMC could effectively alleviate chattering phenomena in conventional SMC and maintain good robustness. An adaptive control intended to counteract parametric uncertainties and external load disturbance is deduced.